Health and criminal profile indicators of incarcerated men - Padilha Kuhn, Carolina (2024)
Understanding the profile of individual deprived of liberty is essential to work on alternatives that minimize recidivism. Thus, this study aimed screen for health indicators and criminal profile in a sample of prisoners, across a cross-sectional study. Data were collected from 134 individuals from a penitentiary in the Paraná State (Brazil). Sociodemographic variables, health indicators, types of crimes, aggression levels, and recidivism were investigated. In total, it was possible to identify a young population (35,93±12,54 years old), with low education (until 8 years), being crimes against the sexual dignity the most common (29,19%). Health indicators revealed that 11,94% reported excellent health, 16,42% very good, 29,85% good, 29,85% reasonable and 11,19% reported bad health. In relation to nutritional profile, the BMI was 27,37±5,34 kg/m², with a predominance of individuals in eutrophic state (35,07%) and underweight (33,58%). According to mental health, the mean of sleep hours was 7,82±2,38 hours/day and most of individuals presented signs and symptoms of depression (53,1%) and anxiety (41,5%). The significant predictors of a negative self-perception about the own health were the presence of depression (OR = 6,31, 95%CI: 1,39 – 28,54) and anxiety (OR = 4,83, 95%CI: 1,26 – 18,39) which, together, explained around 40% of the outcome. The observed profiled resembles national data with this population, hence highlighting the importance of public policies encouraging education, social reintegration, and professional training for young people so they are not tempted to crimes.